Human Immunodeficiency Virus Type 1 Gag-Specific Mucosal Immunity after Oral Immunization with Papillomavirus Pseudoviruses Encoding Gag - Zhang, Hongtao (American Society for Microbiology, 2004)
Mucosal surfaces are the primary portals for human immunodeficiency virus (HIV) transmission. Because systemic immunization, in general, does not induce effective mucosal immune responses, a mucosal HIV vaccine is urgently needed. For this study, we developed papillomavirus pseudoviruses that express HIV-1 Gag. The pseudoviruses are synthetic, nonreplicating viruses, yet they can produce antigens for a long time in the immune system. Here we show that oral immunization of mice by the use of papillomavirus pseudoviruses encoding Gag generated mucosal and systemic Gag-specific cytotoxic T lymphocytes that effectively lysed Gag-expressing target cells. Furthermore, the pseudoviruses generated Gag-specific gamma interferon-producing T cells and serum immunoglobulin G (IgG) and mucosal IgA. In contrast, oral immunization with plasmid DNA encoding HIV-1 Gag did not induce specific immune responses. Importantly, oral immunization with the pseudoviruses induced Gag-specific memory cytotoxic T lymphocytes and protected mice against a rectal mucosal challenge with a recombinant vaccinia virus expressing HIV-1 Gag. Thus, papillomavirus pseudoviruses encoding Gag are a promising mucosal vaccine against AIDS.